177Lu-FA-DOTA-PEG-PLGA Nanoparticles Show Antitumor Efficiency in Targeting Ovarian Cancer - Ziming Guo; Yi Du; Jun Zhao; Sha Sha; Jian Wang (IMR Press, 2024)
Background: The development of novel therapies holds significance in improving the prognosis of ovarian cancer (OC). This study aimed to prepare 177Lu-FA-DOTA-PEG-PLGA nanoparticles and evaluate their antitumor efficacy in OC. Methods: To obtain nanoparticles with both targeting and degradable properties, we employed folate receptor (FR) as the targeting molecule, the biodegradable material polyethyleneglycol-polylactic acid-co-glycolic acid (PEG-PLGA) as the carrier matrix, and diethylene triamine pentaacetic acid (DOTA) as the metal chelating agent to prepare 177Lu-FA-DOTA-PEG-PLGA nanoparticles. The labeling yield and radiochemical purity were determined. Healthy Institute of Cancer Research (ICR) mice and Bagg albino strain C (BALB/c) nude mice bearing subcutaneously transplanted SKOV3 human OC tumors were given 18.5 Mbq of 177Lu-FA-DOTA-PEG-PLGA nanoparticles for histological distribution analysis and micro-single-photon emission computed tomography/computed tomography (micro-SPECT/CT) imaging, respectively. Twelve BALB/c nude mice bearing subcutaneously transplanted tumors or 12 BALB/c nude mice bearing intraperitoneal metastatic tumors were assigned to control (received 0.1 mL saline solution), chemotherapy (received twice 3 mg/kg cisplatin per week), and nanoparticle groups (received 18.5 Mbq nanoparticles via tail vein or intraperitoneal injection) (n = 4 per group). Tumor growth inhibition (TGI) and ascitic fluid volume were calculated to investigate antitumor efficiency. Hematoxylin and eosin (HE) staining was performed to evaluate the safety of nanoparticles. Results: The 177Lu-FA-DOTA-PEG-PLGA nanoparticles (labeling yield: 97-98%; radiochemical purity: 96-98%) exhibited a long blood circulation time and a low renal radioactivity uptake (1.646 %ID/g). Micro-SPECT/CT imaging revealed the highest tumor-to-muscle uptake ratio of 2.81 at 24 h. After tail vein injection of nanoparticles, the tumor growth in the chemotherapy and nanoparticle groups was inhibited compared with the control group. Upon intraperitoneal injection, fluorescence intensities of intraperitoneal metastatic tumors in the control, chemotherapy and nanoparticle groups showed a statistical difference (F = 6.09, p = 0.029). Ascitic fluid volumes in the chemotherapy and nanoparticle groups were significantly lower than that in the control group (F = 13.43, p = 0.006). HE staining results showed no obvious abnormalities in the small intestine and colon tissues of the mice in the nanoparticle group compared to the control group. Conclusions: We successfully developed 177Lu-FA-DOTA-PEG-PLGA nanoparticles with a long blood circulation time and low renal radioactivity uptake. These nanoparticles could inhibit OC tumor growth and intraperitoneal metastasis, suggesting a potential novel therapy for OC patients.